2013
DOI: 10.1016/j.yexmp.2012.07.002
|View full text |Cite
|
Sign up to set email alerts
|

Non-formalin fixative versus formalin-fixed tissue: A comparison of histology and RNA quality

Abstract: Preanalytical handling of tissue samples can influence bioanalyte quality and ultimately outcome of analytical results. The aim of this study was to compare RNA quality, performance in real time RT PCR and histology of formalin-fixed tissue to that of tissue fixed and stabilized with a formalin-free fixative, the PAXgene Tissue System (PAXgene), in an animal model under highly controlled preanalytical conditions. Samples of rat liver, kidney, spleen, intestine, lung, heart muscle, brain, and stomach tissue wer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
94
3

Year Published

2013
2013
2021
2021

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 110 publications
(105 citation statements)
references
References 26 publications
7
94
3
Order By: Relevance
“…The PAXgene Tissue System is a recently developed tissue stabilization technology. So far, researchers have reported that RNA and DNA purified from PAXgene-fixed tissues are of high integrity and that they perform as well as those from fresh frozen tissue [15,16,17]. …”
Section: Methodsmentioning
confidence: 99%
“…The PAXgene Tissue System is a recently developed tissue stabilization technology. So far, researchers have reported that RNA and DNA purified from PAXgene-fixed tissues are of high integrity and that they perform as well as those from fresh frozen tissue [15,16,17]. …”
Section: Methodsmentioning
confidence: 99%
“…21 For molecular analysis, PAXgene preserves RNA better than does formalin. 130 The immunoreactivity of antigens in fixed and paraffinembedded tissue varies markedly depending on the antigen and more specifically on the epitope recognized by the antibody. 8,59 In a comparison of the effect of different fixatives (strong cross-linkers, weak cross-linkers, coagulant, and combination coagulant/cross-linkers) on antigen immunoreactivity in mouse tissue, formaldehyde, followed by the combination fixatives, performed better than the other types.…”
mentioning
confidence: 99%
“…In LM procedures using paraffin as a tissue support, the crystalline nature of the paraffin interferes with the visualization of the cells due to the refraction of the light as it passes through the paraffin. Furthermore, loss of biological molecules in the form of RNA happens as the paraffin is dissolved away (Jonsson & Lagerstedt 1958;Nair 1958;Groelz et al 2013;Staff et al 2013). As can be imagined, this situation may be particularly problematic for small RNA species like microRNAs (miRNAs) that would be easily liberated from the section.…”
Section: Resultsmentioning
confidence: 99%
“…However, for studies focused on gene expression, the paraffin-embedding procedure has drawbacks. The major drawback of paraffin is contamination with RNAses, resulting in RNA degradation (Jonsson & Lagerstedt 1957;Nair 1958;Groelz et al 2013;Staff et al 2013). Furthermore, some of the early steps in the paraffin embedding procedure, prior to the casting of tissue into molds, involve temperatures >50°C which has negative impacts on the tissue.…”
Section: The Isolation Of Cells For Biological Analysesmentioning
confidence: 99%